2016
DOI: 10.1091/mbc.e16-04-0241
|View full text |Cite
|
Sign up to set email alerts
|

The role of HYAL2 in LSS-induced glycocalyx impairment and the PKA-mediated decrease in eNOS–Ser-633 phosphorylation and nitric oxide production

Abstract: This study examines the mechanism of glycocalyx injury under low shear stress (LSS). LSS-induced changes of eNOS phosphorylation and NO production are based on the deficiency of the glycocalyx barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 38 publications
(53 reference statements)
3
24
0
Order By: Relevance
“…These sites are characterized by LSS, which is correlated with reduced glycocalyx dimensions, potentially contributing to leukocyte adhesion and atherosclerotic-lesion development (17). Our previous studies found that LSS activation of HYAL2 degraded HA within the endothelial glycocalyx layer, decreasing eNOS-Ser633 phosphorylation and NO production (7). In the present study, we provided further evidence that glycocalyx impairment in response to LSS is mediated through the inactivation of AMPK and an increase in NHE1mediated HA degradation.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…These sites are characterized by LSS, which is correlated with reduced glycocalyx dimensions, potentially contributing to leukocyte adhesion and atherosclerotic-lesion development (17). Our previous studies found that LSS activation of HYAL2 degraded HA within the endothelial glycocalyx layer, decreasing eNOS-Ser633 phosphorylation and NO production (7). In the present study, we provided further evidence that glycocalyx impairment in response to LSS is mediated through the inactivation of AMPK and an increase in NHE1mediated HA degradation.…”
Section: Discussionsupporting
confidence: 70%
“…Our previous study had suggested that HYAL2 participates in glycocalyx impairment in response to LSS (7). In the present study, we incubated HUVECs with 50 mM of the HYAL2 inhibitor hyaluromycin for 3 h prior to a 30-min LSS exposure.…”
Section: Lss Activates Hyal2 To Degrade Endothelial Glycocalyxmentioning
confidence: 82%
See 2 more Smart Citations
“…We further discovered that LSS strongly activated hyaluronidase 2 to degrade HA in the glycocalyx. The dephosphorylation of eNOS‐Ser‐633 under LSS was triggered after HA degradation by hyaluronidase, and prevented by repairing the glycocalyx with high molecular weight hyaluronan …”
Section: Discussionmentioning
confidence: 99%